Journal of medical signals and sensors
Journal of Medical Signal & Sensors (JMSS) is a quarterly publication by Medical Image and Signal Processing Research Center, designed to provide rapid dissemination of original, cutting-edge ideas and timely, significant contributions in medical (multi-dimensional) signal processing, data analysis and bioinstruments.